2000
DOI: 10.1097/00001756-200008030-00002
|View full text |Cite
|
Sign up to set email alerts
|

Why canʼt you tickle yourself?

Abstract: It is well known that you cannot tickle yourself. Here, we discuss the proposal that such attenuation of self-produced tactile stimulation is due to the sensory predictions made by an internal forward model of the motor system. A forward model predicts the sensory consequences of a movement based on the motor command. When a movement is self-produced, its sensory consequences can be accurately predicted, and this prediction can be used to attenuate the sensory effects of the movement. Studies are reviewed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
554
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 779 publications
(580 citation statements)
references
References 17 publications
24
554
1
1
Order By: Relevance
“…This comparison is thought to occur through efference copies or corollary discharges of the movement (von Holst, 1954;Sperry, 1950). These two aspects of predictive forward models, the prediction about an action (Wolpert et al, 1995) and the comparison of the predicted effects to the actual effect (Blakemore, Wolpert, & Frith, 2000), are thought to contribute to the causal associations we make between our actions and their sensory consequences (David et al, 2008). Recently it has been suggested that a similar predictive process is involved when we observe othersʼ goal-directed actions; that is, we predict the goals, intentions, and consequences of othersʼ actions through an internal representation of the observed action (Kilner, Friston, & Frith, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This comparison is thought to occur through efference copies or corollary discharges of the movement (von Holst, 1954;Sperry, 1950). These two aspects of predictive forward models, the prediction about an action (Wolpert et al, 1995) and the comparison of the predicted effects to the actual effect (Blakemore, Wolpert, & Frith, 2000), are thought to contribute to the causal associations we make between our actions and their sensory consequences (David et al, 2008). Recently it has been suggested that a similar predictive process is involved when we observe othersʼ goal-directed actions; that is, we predict the goals, intentions, and consequences of othersʼ actions through an internal representation of the observed action (Kilner, Friston, & Frith, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While the IM is mainly required for motor control, the FM has been proposed as a possible model for a number of important issues, among which are sensory cancelation (Blakemore et al, 2000), state estimation (Wolpert et al, 1995), and body map acquisition (Schillaci et al, 2012a).…”
Section: Internal Modelsmentioning
confidence: 99%
“…Based on extensive empirical evidence of its putative functionality in the Central Nervous System (Kawato, 1999;Blakemore et al, 2000;Wolpert et al, 2001), Forward and Inverse Models provide arguably a sound epistemological basis to understand cognitive processes at a certain level of description under the embodied cognition framework.…”
Section: Introductionmentioning
confidence: 99%
“…First, we gathered the data set necessary to compute the velocity-dependent ego-vibration magnitude spectrum estimates |N (f,Θ i )| defined in Equation (5). Joint velocities were obtained from the ROS Diamondback pr2 mechanism model class, which reports velocities using firstorder differentiation of encoder readings.…”
Section: Pr2 Implementation Detailsmentioning
confidence: 99%
“…The human central nervous system is believed to use the motor commands sent to the muscles to predict the sensory consequences of movement. These predictions allow one to distinguish self-produced sensations from those arising from external events [5].…”
Section: Introductionmentioning
confidence: 99%